2012
DOI: 10.1111/j.1349-7006.2012.02296.x
|View full text |Cite
|
Sign up to set email alerts
|

Sorting nexin 5 of a new diagnostic marker of papillary thyroid carcinoma regulates Caspase‐2

Abstract: Papillary thyroid carcinoma (PTC) is a well-differentiated endocrine malignant tumor that develops from thyroid follicular epithelium. The tumor represents the most common type of endocrine malignancy; however, its tumorigenesis is not fully elucidated. The aim of this study was to address the functional role of the sorting nexin (SNX) family in PTC because of recent experimental evidence suggesting that the SNX family members actively control endocytotic transportation as well as cell fate. Expression profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…These findings suggest that cell growth signals are primarily induced in Snx5 −/− thyrocytes. No significant changes were observed in the levels of an apoptosis‐related protein, caspase 2, which was upregulated in Snx5‐overexpressing epithelial cells in our in vitro study (Figure G) .…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…These findings suggest that cell growth signals are primarily induced in Snx5 −/− thyrocytes. No significant changes were observed in the levels of an apoptosis‐related protein, caspase 2, which was upregulated in Snx5‐overexpressing epithelial cells in our in vitro study (Figure G) .…”
Section: Resultsmentioning
confidence: 54%
“…Band intensities were measured using ImageJ software. Immunohistochemistry and immunofluorescence laser confocal microscopy were conducted under ELYRAS.1 LSM780 (Carl Zeiss, Oberkochen, Germany) as described previously . For analyzing endosomes, primary thyrocytes were seeded onto a glass‐base confocal dish with DMEM containing 10% FBS at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sorting nexins as PI3P-binding proteins actively determine cell fate through diverse functions in cell signalling, protein-protein/lipid interaction, organelle movement, receptor downregulation and membrane trafficking (Chen et al 2013;Nguyen et al 2006;Danson et al 2013;Pons et al 2012). It is well demonstrated that abnormalities of intracellular vesicles in endosome network occur in many tumor cells (Ara et al 2012). Also, dysfunctions of sorting proteins can alter cell surface receptors and signalling cascades in cells and can eventually cause of induction of tumorogenesis.…”
Section: Discussionmentioning
confidence: 99%